DESIGN OF RETAINING WALLS FOR THE KUSAN RIVER CLIFF STA 4+509 to 4+628 BINAWARA VILLAGE, TANAH BUMBU REGENCY - Silfiana, Silfiana; Afrila, Humaira; Fitriati, Ulfa (Universitas Lambung Mangkurat, 2026)
In Tanah Bumbu Regency, specifically the Binawara Village road plays a crucial role as the sole access road for road users. This landslide is thought to have been caused by high tides in the river alongside the road. The construction of a retaining wall in the form of a sheet pile was part of the Kusan River Bank Reinforcement Project in Binawara Village, Tanah Bumbu Regency, South Kalimantan Province. The landslide is 119 meters long, 6 meters wide, and 8 meters high. The erosion of the river water, which is increasingly wearing away at the cliff, will cause a landslide on the road.The design of this retaining wall began with a literature study, collecting and studying previous literature related to the design. This was followed by data collection and soil investigation. This was followed by a stability analysis of the existing retaining wall. This was then modeled and analyzed using Geostudio 2024 software to obtain a safety factor. Finally, the retaining wall and overall stability were calculated.From the results of the stability analysis of the existing retaining wall, a safety factor of 0.995 <1.5 was obtained, which means the slope is not safe. In the calculation of the depth D_design, it was obtained in the sheet pile of D = 9 m. So the total sheet pile length is 17 m. The maximum moment obtained from the calculation was 22.58 t.m, while the cracking moment of the concrete sheet pile type was 23.40 t.m. The maximum moment <cracking moment was obtained, so the sheet pile construction was declared safe. The anchor force obtained was 56.51 tons/m. If a tie rod with s = 1 m was installed, the anchor force that occurred was 7.06 tons/m. With the ST-44 steel quality design, the tie rod diameter was 350.14 cm^3. Based on the results of the overall stability, it can be concluded that it has met the requirements and can be declared safe (SF 2.027 > 1.5). Keywords: Retaining Wall, Sheet Pile, Overall stability, safety factor, anchorage.